PLGA-encapsulated tea polyphenols enhance the chemotherapeutic efficacy of cisplatin against human cancer cells and mice bearing Ehrlich ascites carcinoma - Singh M (Dove Medical Press, 2015)
Madhulika Singh,1 Priyanka Bhatnagar,2 Sanjay Mishra,1 Pradeep Kumar,2 Yogeshwer Shukla,1 Kailash Chand Gupta1,2 1CSIR-Indian Institute of Toxicology Research, Lucknow, 2CSIR-Institute of Genomics and Integrative Biology, Delhi University Campus, Delhi, India Abstract: The clinical success of the applicability of tea polyphenols awaits efficient systemic delivery and bioavailability. Herein, following the concept of nanochemoprevention, which uses nanotechnology for enhancing the efficacy of chemotherapeutic drugs, we employed tea polyphenols, namely theaflavin (TF) and epigallocatechin-3-gallate (EGCG) encapsulated in a biodegradable nanoparticulate formulation based on poly(lactide-co-glycolide) (PLGA) with approximately 26% and 18% encapsulation efficiency, respectively. It was observed that TF/EGCG encapsulated PLGA nanoparticles (NPs) offered an up to ~7-fold dose advantage when compared with bulk TF/EGCG in terms of exerting its antiproliferative effects and also enhanced the anticancer potential of cisplatin (CDDP) in A549 (lung carcinoma), HeLa (cervical carcinoma), and THP-1 (acute monocytic leukemia) cells. Cell cycle analysis revealed that TF/EGCG-NPs were more efficient than bulk TF/EGCG in sensitizing A549 cells to CDDP-induced apoptosis, with a dose advantage of up to 20-fold. Further, TF/EGCG-NPs, alone or in combination with CDDP, were more effective in inhibiting NF-κB activation and in suppressing the expression of cyclin D1, matrix metalloproteinase-9, and vascular endothelial growth factor, involved in cell proliferation, metastasis, and angiogenesis, respectively. EGCG and TF-NPs were also found to be more effective than bulk TF/EGCG in inducing the cleavage of caspase-3 and caspase-9 and Bax/Bcl2 ratio in favor of apoptosis. Further, in vivo evaluation of these NPs in combination with CDDP showed an increase in life span (P<0.05) in mice bearing Ehrlich’s ascites carcinoma cells, with apparent regression of tumor volume in comparison with mice treated with bulk doses with CDDP. These results indicate that EGCG and TF-NPs have superior cancer chemosensitization activity when compared with bulk TF/EGCG. Keywords: anticancer, poly(lactide-co-glycolide), nanoparticles, cisplatin, tea polyphenols